2013
DOI: 10.1186/1476-7120-11-45
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricle function in aortic stenosis: mitral annular plane systolic excursion is not inferior to speckle tracking echocardiography derived global longitudinal peak strain

Abstract: BackgroundEarly detection of left ventricle (LV) systolic dysfunction is essential for management of patients with aortic stenosis (AS). Two- dimensional speckle tracking derived global longitudinal peak strain (GLPS) is more sensitive than ejection fraction (EF) but requires good image quality and is not easily accessible. The aim of the study was to compare GLPS with traditional echocardiographic parameter- mitral annular plane systolic excursion (MAPSE) in AS.Material and methodsIn consecutive patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
(40 reference statements)
0
13
0
1
Order By: Relevance
“…Firstly, MAPSE was decreased even in early stages of twin-to-twin transfusion syndrome before and after laser surgery [ 32 ]. Secondly, MAPSE has been reported not to be inferior to speckle tracking echocardiography derived global longitudinal peak strain for the determination of LV deterioration in aortic stenosis [ 33 ]. Recently, MAPSE was utilized as the functional reference to measure systolic LV longitudinal deformation in a study analyzing tortuosity of the coronary arteries [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, MAPSE was decreased even in early stages of twin-to-twin transfusion syndrome before and after laser surgery [ 32 ]. Secondly, MAPSE has been reported not to be inferior to speckle tracking echocardiography derived global longitudinal peak strain for the determination of LV deterioration in aortic stenosis [ 33 ]. Recently, MAPSE was utilized as the functional reference to measure systolic LV longitudinal deformation in a study analyzing tortuosity of the coronary arteries [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although MAPSE only demonstrates the longitudinal motion of the LV, it was more sensitive than LVEF in detecting early LV dysfunction, such as in hypertensive patients [ 26 , 27 ]. In patients with moderate to severe aortic stenosis, MAPSE was as good as GLS in detecting early LV dysfunction [ 28 ]. Similar to a previous report that showed a positive correlation between MAPSE and longitudinal strain [ 29 ], the present study also found a good correlation between MAPSE sum with LVLS ( r = 0.82).…”
Section: Discussionmentioning
confidence: 99%
“…Published by Sciedu Press curves have been shown to accurately reflect the heart condition, [22,23] its measurement requires good quality clips and complex algorithms. The complexity of these algorithms stems from the derivation of the 2D strain curves from tracking the whole left ventricle concomitantly.…”
Section: Resultsmentioning
confidence: 99%
“…Multidimensional dynamic programing [12] is a more robust technique and much more time consuming method. [22] The computation times reported for multidimensional dynamic programing [12] makes the real time application of this approach more difficult. The algorithm developed here provides results comparable to those obtained with multidimensional dynamic programing with much lower computation times.…”
Section: Discussionmentioning
confidence: 99%